2000
DOI: 10.1001/archinte.160.14.2150
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Improved Weight Loss With a Prepared Meal Plan in Overweight and Obese Patients

Abstract: Long-term dietary interventions induced significant weight loss and improved cardiovascular risk in high-risk patients. The prepared meal plan simultaneously provided the simplicity and nutrient composition necessary to maintain long-term compliance and to reduce cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
1
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 27 publications
(21 reference statements)
5
118
1
4
Order By: Relevance
“…In contrast to studies that report enhanced quality of life in association with a diet intervention program [Metz et al, 2000;McCarron, 1997], the participants in the intervention group in this study did not observe a marked increase in their quality of life. Higher level of education and socioeconomic status of the participants in both groups may have been the neutralizing factor.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to studies that report enhanced quality of life in association with a diet intervention program [Metz et al, 2000;McCarron, 1997], the participants in the intervention group in this study did not observe a marked increase in their quality of life. Higher level of education and socioeconomic status of the participants in both groups may have been the neutralizing factor.…”
Section: Discussioncontrasting
confidence: 99%
“…At the end of the eight-week intervention period, the DASH trial researchers found improvement in healthrelated quality of life scores in all treatment groups. Similar findings were reported from another study that examined the effects of a prepared meal plan on weight loss and cardiovascular risk factors [Metz et al, 2000]. Similar to the DASH study, the investigators found improvements in quality of life in the intervention group.…”
Section: Introductionsupporting
confidence: 80%
“…Vitamins, minerals, and fiber may also be included. Use of meal replacements once or twice daily to replace a usual meal can result in significant weight loss (331)(332)(333)(334)(335). Presumably the meal replacement causes a reduction in energy intake by eliminating the choice of type and amount of food.…”
Section: Energy Balance and Obesitymentioning
confidence: 99%
“…Breakfast cereals have been used as a meal replacement to effectively reduce meal intake and produce significant weight loss (51,52) . Similarly, pre-packaged meals have been shown to produce a significant weight loss (53)(54)(55)(56)(57) . These meals consist of commercial-grade, ready-prepared foods, packaged in smaller sizes than would ordinarily be served.…”
Section: Will-power Is Insufficient To Control Eating Behaviourmentioning
confidence: 99%